Back on track? Savings puzzles in EU-accession countries - Mechthild Schrooten; Sabine Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
After the collapse in the early years of transition, saving rates in many EU-accession countries have recovered and remained stable during recent years. This may indicate that the transformation process has come to an end with regard to savings. Is saving behaviour in EU-accession countries now driven by the same forces as it is in market economies? We use a panel data set covering the years 1990 to 1999 to estimate fixed-effects models for domestic and private saving ratios. Central findings: saving is highly persistent; income, growth and institutional reforms cause saving to increase, whereas public saving crowds out private saving. Domestic saving and foreign capital are operating as substitutes.
Keywords: C33; P2; E21; 330; Panel data; savings; EU-accession countries; transformation; Sparen; Übergangswirtschaft; Schätzung; Osteuropa